Investigating the impact of gamification on customer engagement, brand loyalty and purchase intent in marketing - Punwatkar, S.; Verghese, M. (Journal of Applied Research and Technology, 2025)
Gamification has evolved as a potent method for engaging and motivating consumers in today's dynamic market scenario. This research report investigates the impact of gamification on customer purchasing intentions to determine its current relevance. This study investigates the subtle links between gamification aspects, user engagement, brand loyalty, and consumer purchasing intentions using Partial Least Squares Structural Equation Modelling (PLS-SEM). Gamification is an important technique in modern marketing approaches because of its capacity to captivate and incentivize people. The survey included 300+ individuals from Durg and Raipur, Chhattisgarh's two major districts, representing a broad demographic. The findings show that Gamification has a large indirect effect on Customer Engagement, which in turn affects Brand Loyalty and eventually shapes Customer Buying Intentions. This study emphasises the critical significance of gamification in altering customer behaviour and the relevance of promoting User Engagement and Brand Loyalty to drive purchasing decisions. Gamification strategy emerges as a powerful force in the contemporary marketing landscape, with the potential to affect the entire customer journey, as firms seek novel methods to connect with consumers.